2022
DOI: 10.1155/2022/1300157
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the Performance of MWCNT/ZnO Hybrid Material with pH for Efficient Antibacterial Agent

Abstract: In the present work, multiwalled carbon nanotube (MWCNT)/zinc oxide (ZnO) nanoparticles at pH 6.0, 7.0, 8.0, and 10.0 were prepared through the coprecipitation method to improve the antibacterial activity. Morphological, structural, and optical analysis, such as Fourier transform infrared spectroscopy, X-ray diffraction, and field emission scanning electron microscopy, was used to investigate the formation of composites. Analysis revealed that there were variations in morphology from agglomerated structures to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…This similarly indicates that ion mobility is improved by disrupting the polymer chain arrangement and creating disorder in the matrix, and this may promote the faster ion dynamics in the matrix that subsequently increase the conductivity of the electrolyte [ 45 ]. Low T g has been linked to a loss in crystallinity due to the addition of a filler substance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This similarly indicates that ion mobility is improved by disrupting the polymer chain arrangement and creating disorder in the matrix, and this may promote the faster ion dynamics in the matrix that subsequently increase the conductivity of the electrolyte [ 45 ]. Low T g has been linked to a loss in crystallinity due to the addition of a filler substance.…”
Section: Resultsmentioning
confidence: 99%
“…The Arrhenius model is a vital factor to study when dealing with the transportation of ions relative to temperature. The observed linear relationship points to a considerable phase transition in the prepared samples, signifying that the temperature dependence of the conductivity might indeed be designated by the Arrhenius model, as in Equation (2) [ 45 ]: where E a is the activation energy, T is the absolute temperature in Kelvin (K), and σ o denotes the pre-exponential factor.…”
Section: Resultsmentioning
confidence: 99%
“…They demonstrated that the synthesized MWCNT/ZnO composite has improved antibacterial properties against Staphylococcus aureus as the zone of inhibition test showed a maximum of 20 mm circular area. In addition, the studies also demonstrated that the antibacterial activity works best when synthesized at pH 10.0 compared to pH 6 and 7 [31].…”
Section: Figure 4 General Representation Of Antibacterial Activity By...mentioning
confidence: 87%
“…As a result, it is assumed that the dopant is evenly distributed in the lattice of ZnO, causing no further changes in the crystal structure [25]. Additional peaks of the diffraction peaks (002) at 26 • and (100) at 43 • , corresponding to functionalized MWCNTs, were visible in the XRD spectrum of La-ZnO/MWCNTs [26].…”
Section: Morphological Elemental and Structural Analysis Of Synthesiz...mentioning
confidence: 99%